Future-Proofing Companies with Climate Strategies - Sim Kee Boon Institute (Institutional Knowledge at Singapore Management University, 2023)
Scientists have shown that humans significantly contributed to global warming through greenhouse gas (GHG) emissions in the last two centuries. The 2022 United Nations (UN) Climate Change Conference (COP27) and 2022 UN Biodiversity Conference (COP15) focused on setting goals and collective action to address and reverse these negative consequences. Climate and sustainability experts discussed key insights from COP27 and COP15 at a recent panel discussion organized by the Sim Kee Boon Institute (SKBI) at SMU.